Beneficial effects of a cognitive-behavioral occupational stress management group training: the mediating role of changing cognitions - Wirtz, Petra H.; Auer, Alisa; Semmer, Norbert K.; Ehlert, Ulrike; Nussbeck, Fridtjof W. (Frontiers in Psychology, 2024)
Introduction While the effectiveness of cognitive-behavioral stress management trainings (SMTs) is well-documented, the underlying mechanisms, especially in an occupational context, are not fully understood. We tested whether SMT-induced improvements in stress management skills, particularly in the mastery of changing cognitions, may explain beneficial SMT effects. Methods Our non-randomized controlled trial comprised 108 employees of a German health insurance company, with 65 of them participating in a cognitive-behavioral SMT and 43 participating in an alternative control training (AT). As outcome variables, we repeatedly assessed stress-related (functional stress management skills, relaxation, stress reactivity, exhaustion), work-related (job dissatisfaction), and specific-context-related (social support, trait anger) measures at baseline, 2 weeks, and 3 months after the trainings. Functional stress management skills and, in particular, a subscale assessing perceived mastery of changing cognitions (“cognitive-strategies-and-problem-solving”) were tested as mediators of change. Results Repeated measures (M)AN(C)OVAs and complementary multigroup latent difference models confirmed improvements in all outcomes in the SMT-group compared to the AT-group (p's ≤ 0.015). Multivariate mediation path analyses revealed that, regarding mechanisms of change, the subscale cognitive-strategies-and-problem-solving was identified as the most important mediator for all outcomes (95% CIs for expected increases in SMT- vs. AT-group = [lower limits (LLs) ≥ 0.004]; 95% CIs for expected decreases in the SMT- vs. AT-group = [upper limits(ULs) ≤ −0.078]) except for job dissatisfaction. Discussion Our findings confirm that employees can effectively learn to master stress reduction techniques and consequently lower the resulting burden. Moreover, beneficial SMT effects seem to result from improvements in functional stress management skills, particularly in the ability to change cognitions. This points to the importance of training cognitive techniques.